Simulasi Sistem Otomasi Sederhana Pada Light Emitting Diode (LED) Berjalan di Sekolah Menengah Atas Negeri 6 Kabupaten Kepahyang - Yoli Andi Rozzi; Siswanto Siswanto; Devi Sartika; Eko Suryana; Agung Pradana; Nanda Eka Juniawan (Universitas Dehasen Bengkulu, 2023)
Community service activities in the form of socialization and practice regarding simple automation system simulations on running Light Emitting Diode (LED) have the aim of providing knowledge and information to students at SMAN 6 Kepahyang Regency so that they gain knowledge about current technological advances. The subjects in this community service activity were students at SMAN 6 Kepahyang Regency. The socialization process is carried out by providing information and hands-on practice in assembling components of a simple automation system simulation on a running Light Emitting Diode (LED). Where the running LED simulation is an example of a simple implementation of a simple automation system from artificial intelligence (Artificial Intelligence). In practice, the system will use the Arduino Uno Microcontroller for data processing. Then the result of this community service activity is that students at SMAN 6 Kepahyang Regency will gain knowledge about current technological advances, besides that students at SMAN 6 Kepahyang Regency are also expected to be able to develop more creative and innovative ideas related to technological developments that exists. The conclusions obtained from carrying out community service activities, especially students at SMAN 6 Kepahyang Regency are in the form of obtaining knowledge and information regarding simple automation systems on Light Emitting Diode (LED) running on the implementation of artificial intelligence (Artificial Intelligence), knowing what electronic components can be used in a simple automation system simulation on a running Light Emitting Diode (LED), practice directly in making a simple automation system simulation circuit on a running Light Emitting Diode (LED). Then through socialization and hands-on practice students at SMAN 6 Kepahyang Regency can gain knowledge so that in the future it is hoped that they will be able to develop more creative and innovative ideas, especially in the field of technology and information advancement.